Safety and Phosphate‐Binding Capacity of Oxylanthanum Carbonate in Healthy Volunteers - Pablo E. Pergola; Melanie S. Joy; Armando Garsd; Steve J. Hasal; Atul Khare; Guru Reddy; Pramod Gupta; William F. Finn (Clinical and Translational Science)
ABSTRACT Despite the widespread use of currently available serum phosphate management options, elevated serum phosphate is common in patients with end‐stage kidney disease on dialysis. Characteristics of currently available phosphate binders that lead to poor patient experiences such as large drug volume size of required daily medication (e.g., many large tablets) and adverse gastrointestinal effects may decrease compliance to labeled dosing instructions, thus decreasing their efficacy. Oxylanthanum carbonate is a new molecule yielding the same phosphate‐binding capacity as lanthanum carbonate, but in a much smaller drug volume and tablet size. It is formulated as small tablets that can be easily swallowed. In a double‐blind dose‐escalation phase 1 study, healthy volunteers (n = 32) were randomly divided into four treatment arms and randomly assigned to receive oxylanthanum carbonate tablets or a placebo over a period of 4 days to evaluate safety, urinary and fecal excretion of phosphorus, and pharmacokinetics. Each treatment arm evaluated a different dose of oxylanthanum carbonate: 500, 1000, 1500, or 2000 mg three times a day (TID). The study drug was well‐tolerated. Oxylanthanum carbonate effectively decreased dietary phosphorus absorption, demonstrated by decreased urinary phosphorus excretion and increased fecal phosphorus excretion. Systemic absorption of oxylanthanum carbonate was minimal, with lanthanum serum concentration values below the level of quantification (0.500 ng/mL) in all subjects receiving 500 mg TID and did not exceed 0.7 ng/mL at other doses. Future studies should evaluate and confirm the ability of oxylanthanum carbonate to reduce pill burden and improve dose administration, patient tolerability, adherence, and treatment outcomes. Trial Registration: ClinicalTrials.gov identifier: NCT01560884